The Routledge companion to Northeast India
1 online resource
Keywords: "The Routledge Companion to Northeast India is a trans-disciplinary and comprehensive compendium of a vital yet under-researched region in South Asia. It provides a unique guide to prevailing themes, theories, arguments, and history of Northeast India by discussing its life-forms - human and not - languages, landscapes, and lifeways in all its diversity and difference. The volume contains authoritative entries from leading specialists from and on the region and offers clear, concise, and illuminating explanations of key themes and ideas. A hands-on, practical, and comprehensive guide to Northeast India, this book fills a significant gap in the literature and will be an invaluable teaching, learning and research resource for scholars and students of Northeast India Studies, South Asian and Southeast Asian societies, culture, politics, humanities, and the social sciences in general"--